Evaluation of the Urgency of Unrealized Infrastructure Development in the Mandalika Special Economic Zone Using Structural Equation Model (SEM) Analysis - Johan Jasmadi; Jauhar Fajrin; Made Mahendra (Eduvest - Journal of Universal Studies, 2026)
The development of the Mandalika Special Economic Zone (SEZ) faces challenges related to infrastructure that has not been fully realized, which may affect the effectiveness of the area. Adequate infrastructure is essential to support the competitiveness and sustainability of the Mandalika SEZ as a leading tourism destination. This study aims to identify the factors that influence the urgency of infrastructure development, analyze the relationships among variables, and determine the infrastructure priorities that need to be addressed immediately. This study uses an explanatory quantitative approach through stakeholder surveys and Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis. The exogenous variables include infrastructure-related factors, while the endogenous variables include socioeconomic benefits, sustainability, community welfare, and tourism attractiveness. The results of the analysis show that the priorities for infrastructure development are as follows: 1) regional supporting infrastructure, 2) electricity facilities, 3) SWTP, 4) infrastructure for surrounding communities, 5) clean water and irrigation systems, and 6) WWTP. Regional supporting infrastructure has the greatest influence on socioeconomic benefits and destination attractiveness. Infrastructure development in the Mandalika SEZ needs to prioritize a value-creating infrastructure approach to improve the competitiveness and sustainability of the region. These findings provide a scientific basis for more strategic and sustainable infrastructure development planning.